Dependable control systems with Internet of Things. (November 2015) - Tran, Tri; Ha, Q.P.
Abstract: This paper presents an Internet of Things (IoT)-enabled dependable control system (DepCS) for continuous processes. In a DepCS, an actuator and a transmitter form a regulatory control loop. Each processor inside such actuator and transmitter is designed as a computational platform implementing the feedback control algorithm. The connections between actuators and transmitters via IoT create a reliable backbone for a DepCS. The centralized input–output marshaling system is not required in DepCSs. A state feedback control synthesis method for DepCS applying the self-recovery constraint is presented in the second part of the paper. Abstract : Graphical abstract: Abstract : Highlights: New structure of reliable control systems enabled by IIoT Smart intercommunicating sensors and actuators. Telemetry architecture with local intelligence. Dependable control system (DepCS) to facilitate the autonomous operations. Novel control synthesis method using self-recovery constraint.